Relationships between heart rate variability and performance in youth female field hockey players: ultra-short-term versus criterion measures - Gonzalez-Fimbres, R.; Hernandez-Cruz, G.; Flatt, A. (The Journal of Strength and Conditioning Research, 2021)
Coaches monitor heart rate variability (HRV) in athletes to evaluate training adaptations. Ultra-short-term HRV recordings (i.e., 60 seconds) are becoming more popular among sports teams due to player adherence issues with criterion 5-minute recordings. However, whether ultra-short-term HRV measures provide similar associations as 5-minute measures with performance markers in youth female athletes has yet to be investigated. Purpose: To determine if ultra-short-term and criterion HRV measures are similarly associated with cardio-respiratory and neuro-mucular performance in youth female field hockey players. Methods: Members (n = 11; 16.8 ± 1.1 years; 157.1 ± 5.2 cm; 55.2 ± 5.2 Kg) from the youth female field hockey Mexican National Team participating in a four-week training camp before the 2018 Youth Olympics, took part in this study. Players performed daily HRV measures (5-minute recording follow 1-minute stabilization) with a Smartphone application in the seated position after waking at 6:00 am throughout the four-week camp. The natural logarithm of the root mean square of successive differences (LnRMSSD) was derived from the first min and the full 5-minute segment. The 7-day mean (LnRMSSDm) and coefficient of variation (LnRMSSDcv, a marker of daily fluctuations) were calculated from week 1 and week 4. Before and after the training camp, a series of performance tests were performed including the intermittent fitness test (IFT 30-15), Illinois agility test, 40 m sprint test, and 6 × 30 m repeat sprint ability (RSA) test. The agility, sprinting and RSA tests were measured with an electronic timing system. For relationships between LnRMSSDm, LnRMSSDcv and performance, Pearson's r coefficient was used. Results: Values for LnRMSSD and performance metrics from week 1 and week 4, or pre- and post-camp are presented in Table 1. During week 1, no associations between criterion or ultra-short-term LnRMSSD parameters and performance markers were observed (r = 0.07 - 0.33, all P > 0.05). At week 4, LnRMSSDcv derived from both criterion and ultra-short-term measures were similarly associated (all P < 0.05) with IFT 30-15 (criterion vs. ultra-short-term, r = -0.78 vs. r = -0.71), agility (r = 0.85 vs. r = 0.77), 40 m sprint (r = 0.66 vs. r = 0.76), and RSA (r = 0.81 vs. r = 0.76). Conclusions: LnRMSSDcv from criterion and ultra-short-term recordings were similarly and significantly associated with performance metrics among national level youth female athletes following a training camp. Practical Applications: Players with a more stable LnRMSSD pattern in week 4 (i.e., lower LnRMSSDcv) demonstrated the greatest performance results. This association was observed for both criterion and ultra-short-term measures. Players were exposed to a novel training stimulus which may have confounded associations with performance metrics in week 1. Coaches and sports scientists can use ultra-short-term HRV measures in favor of lengthier criterion measures when monitoring youth female athletes.